Characterization and Fine Mapping of a Novel Rice Narrow Leaf Mutant nal9. Issue 11 (10th September 2013) - Li, Wei; Wu, Chao; Hu, Guocheng; Xing, Li; Qian, Wenjing; Si, Huamin; Sun, Zongxiu; Wang, Xingchun; Fu, Yaping; Liu, Wenzhen
Abstract: A narrow leaf mutant was isolated from transgenic rice ( Oryza sativa L.) lines carrying a T‐DNA insertion. The mutant is characterized by narrow leaves during its whole growth period, and was named nal9 ( narrow leaf 9 ). The mutant also has other phenotypes, such as light green leaves at the seedling stage, reduced plant height, a small panicle and increased tillering. Genetic analysis revealed that the mutation is controlled by a single recessive gene. A hygromycin resistance assay showed that the mutation was not caused by T‐DNA insertion, so a map‐based cloning strategy was employed to isolate the nal9 gene. The mutant individuals from the F2 generations of a cross between the nal9 mutant and Longtepu were used for mapping. With 24 F2 mutants, the nal9 gene was preliminarily mapped near the marker RM156 on the chromosome 3. New INDEL markers were then designed based on the sequence differences between japonica and indica at the region near RM156. The nal9 gene was finally located in a 69.3 kb region between the markers V239B and V239G within BAC OJ1212_C05 by chromosome walking. Sequence and expression analysis showed that an ATP‐dependent Clp protease proteolytic subunit gene ( ClpP ) was most likely to be the nal9 gene. Furthermore, the nal9 mutation was rescued by transformation of the ClpP cDNA driven by the 35S promoter. Accordingly, the ClpP gene was identified as the NAL9 gene. Our results provide a basis for functional studies of NAL9 in future work.